EFL Learners' Perceptions on Flipped Classroom in a Private University in Indonesia - Akib, Muhaiminah; Abduh, Amirullah; Sahril, Sahril; Syahrianti, Syahrianti; Firman, Firman (Universitas Negeri Makassar, 2025)
This research will analyze the students’ perception about flipped classroom. This study used a qualitative case-study approach. conducted at Universitas Muhammadiyah Sorong. The subjects of this research are 20 subjects. The findings of the study shows that three important patterns emerged from the data. The first theme, structure learning approach, includes sub-themes that define the flipped classroom: preparatory aspects, procedural views, and structured processes. The second theme, creating enjoyable atmosphere, is further divided into several sub-themes: engagement through active learning, personalized and flexible learning, and supportive classroom culture. The final theme, fostering independent learning activities, encompasses sub-themes such as learning without direct teacher guidance, developing problem-solving skills, and managing their time effectively. The findings of this study imply that the flipped classroom model can be highly effective in higher education by promoting a more structured and engaging learning environment.